2001
DOI: 10.1111/j.1365-2621.2001.tb11333.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tissue Infrastructure on Electric Conductance of Vegetable Stems

Abstract: This study measures the electric conductance and examines the microscopic structure of bamboo shoots, sugarcane, lettuce stem, and mustard stem. The electric conductance readings vary from 0.09 S/m to 0.72 S/m across the stem, and from 0.19 S/m to 0.46 S/m along the stem. The electric conductance along the stem is higher than the electric conductance across the stem in bamboo shoots and sugarcane, while the reverse is true in lettuce stem and mustard stem. The orientation of vascular bundles and the shape of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
(8 reference statements)
0
13
0
1
Order By: Relevance
“…Electrical conductivity can be influenced by temperature (Palaniappan & Sastry, 1991), electrolyte concentration, chemical content (Rieger, 1994), viscosity (Hamann, Hamnett, & Vielstich, 1998), suspended solids (Palaniappan & Sastry, 1991), electrolytic strength (Hamann et al, 1998), and presence of cell structure (Wang, Kuo, Kuo-Huang, & Wu, 2001). Sensitivity to such variables makes EC an indicator of process-induced changes in food systems.…”
Section: Introductionmentioning
confidence: 98%
“…Electrical conductivity can be influenced by temperature (Palaniappan & Sastry, 1991), electrolyte concentration, chemical content (Rieger, 1994), viscosity (Hamann, Hamnett, & Vielstich, 1998), suspended solids (Palaniappan & Sastry, 1991), electrolytic strength (Hamann et al, 1998), and presence of cell structure (Wang, Kuo, Kuo-Huang, & Wu, 2001). Sensitivity to such variables makes EC an indicator of process-induced changes in food systems.…”
Section: Introductionmentioning
confidence: 98%
“…It has been observed that both the orientation of vascular bundles and the shape of parenchyma cells can influence the electrical conductance in vegetables (Wang et al . ). Zareifard et al .…”
Section: Introductionmentioning
confidence: 97%
“…The electrical conductivity of a material represents its ability to transport electric charge, and its measurement provides a direct measurement of ionic behavior in electrolyte solutions (Kissinger and Heineman, 1996;Min et al, 2007). Various factors can influence electrical conductivity measurements including temperature, electrolyte concentration, suspended solids and cell structure (Min et al, 2007;Wang et al, 2001). Palta et al (1977a,b) utilized electrical conductivity measurement to investigate the mechanism of freeze injury of onion cells.…”
Section: Introductionmentioning
confidence: 98%